2008
DOI: 10.1111/j.1540-8159.2008.01118.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Continuous and Triggered Atrial Overdrive Pacing on Paroxysmal Atrial Fibrillation in Pacemaker Patients

Abstract: Triggered atrial pacing functions alone resulted in a low AF burden. The additional activation of continuous atrial overdrive pacing increased the percentage of atrial pacing, but had no beneficial effects on the prevention of paroxysmal AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…That study showed a limited reduction of AF burden (0.08 hours/day) in the treatment arm 15 . Other preventive atrial pacing strategies such as atrial pacing in response to atrial premature beats, postexercise pacing, and continuous pacing have been developed but unfortunately, these atrial pacing algorithms have not been shown to consistently and substantially reduce the incidence of AF 16–18 …”
Section: Discussionmentioning
confidence: 99%
“…That study showed a limited reduction of AF burden (0.08 hours/day) in the treatment arm 15 . Other preventive atrial pacing strategies such as atrial pacing in response to atrial premature beats, postexercise pacing, and continuous pacing have been developed but unfortunately, these atrial pacing algorithms have not been shown to consistently and substantially reduce the incidence of AF 16–18 …”
Section: Discussionmentioning
confidence: 99%
“…Different pacemaker-specific algorithms including triggered pacing and continuous overdrive atrial pacing were developed to reduce atrial fibrillation. 9–11 , 13 However, the evidence favouring routine use of these algorithms is not convincing. The ASSERT trial showed no benefit of an atrial overdrive pacing algorithm in reducing atrial fibrillation, but a non-significant trend suggested that increased atrial pacing increases the risk of atrial fibrillation.…”
Section: Discussionmentioning
confidence: 99%
“…No effect on the incidence of AF for a continuous overdrive stimulation was observed in several previous studies including OASES (Overdrive Atrial Septum Stimulation) and AFT (Atrial Fibrillation Therapy). Only in the case of triggered pacing a benefit was found, compared to the continuous pacing, irrespective of its rate and a lead location [9,10].…”
mentioning
confidence: 86%